One false note - Korman, Gordon (London : Scholastic, 2008)
A million dollars, or a clue? Police report a break-in at an elite hotel, and the suspects sound suspiciously like Amy and Dan. There's a car and speedboat chase and an angry mob! When there's a Clue on the line, anything can happen.
Keywords: Code and cipher stories; Children's stories